Comparative transcriptome analysis of Pteroceltis tatarinowii Maxim., an endemic fiber tree - Liu, Hui-Jin; Zhang, Li; Xu, Yan-Nian; Zhang, Xiao-Ping; Li, Xiao-Hong (Bangladesh Journal of Botany, 2019)
The bark of Pteroceltis tatarinowii Maxim., an endemic tree in Ulmaceae, is the main raw material for manufacturing Xuan Paper which is widely used in calligraphy and painting field. The characteristics of P. tatarinowii bark is the main limiting factor for the quality of Xuan Paper specially the content of cellulose and lignin. The molecular basis related to cellulose and lignin synthesis in P. tatarinowii would be helpful to understand and seek higher quality raw materials for Xuan Paper. RNA-seq was utilized to reveal transcriptome differences in P. tatarinowii from three far isolated localities (AL, JX and XA) under different climate environments. A total of 290 million reads were generated for further analysis in three libraries. In total, 2,850, 2,038 and 1,986 DEGs were identified in XA, JX and AL, respectively. Compared with the sample from XA, there were 822 up-regulated and 1706 down-regulated in AL sample. AL sample has 611 up-regulated genes and 647 down-regulated genes in comparison with JX sample. Comparing XA and JX samples, 443 were up-regulated and 1,783 were down-regulated in XA. Three samples had similar GO enrichment patterns. There were 19 and 9 genes identified as CESA and CSL (E-value less than 1.0E-20), respectively. Although no significant expression differences were found in three samples, KOB1, GPI-anchored protein gene and CTL1 were differently expressed, and KOB1 and GPI-anchored protein gene were up-regulated in JX. A number of the unigenes (474) that were involved in ‘phenylpropanoid biosynthesis’, were mostly not differently expressed. Only a few genes annotated as PAL, 4CL, C4H and CAD were significantly different in expression. In AL, 3 CAD and 1 PAL were up-regulated, whereas 6 CAD, 3 4CL and 1 HCT were up-regulated in XA, and 1 PAL, 2 4CL, 2 C4H in JX. JX sample had the highest cellulose content and XA sample had the highest lignin content, which being consistent with the hierarchical cluster analysis of differently expressed genes. Differences in the expression of these genes might influence the cellulose and lignin content.